MODIFIED LOW-DOSE FORMALIN PRESERVATION: IN THE ANATOMICAL-SURGICAL DISSECTION & PROSECTED ANATOMICAL MODELS: A CASE REPORT - Veronica, Fifi; Gradia, Resti; Fitri, Lulu L. (Jurnal Kedokteran dan Kesehatan : Publikasi Ilmiah Fakultas Kedokteran Universitas Sriwijaya, 2025)
The development of cadaver preservation has been fast-paced. The subtraction of formalin dose in embalming has been used since many negative factors were found in long-term usage. Preventing putrefaction progress on the cadavers, ensuring no risk of infection when in contact with a dead body, preventing hardening and retention of color tissue and organs, preventing desiccation, inhibit fungal or bacterial growth are the main goals of embalming for anatomical purposes. The new formula has been developed by using low-dose formalin, ethanol, phenol, and sodium chloride (Modified Low-Dose Formalin). This method can be used in practical anatomical-surgical dissection using either cadavers or anatomical models with low-cost maintenance.